Effects of Evidence-Based Teaching in Adult Nursing 2 on Cognitive Skills and 21st Century Skills - PRAMTHAISONG, SAKDA; Sanmorya, Sudawan; Junwijit, Saichol (NU Journal of Nursing and Health Sciences, 2023)
This research is a quasi-experimental research with two-group comparison before and after within the experimental group and compared between the experimental group and the control group. aimed to study the effect of evidence-based teaching in adult nursing 2 on cognitive skills and the 21st century skills subject One hundred and thirty eight 3rd nursing students in Boromarajonani College of Nursing Buddhachinaraj were divided into experimental and control groups, 69 in each group. The control group received lecture and case study, while those in the experimental group received evidence-based teaching method in Adult Nursing 2 The research instruments were learning outcome assessment form. expected behavior according to the framework for qualifications in higher education Cognitive Skills, Content validity index (CVI) was 1.00 and cronbach’s alpha coefficient was .98 and the 21st Century Skills Questionnaire on 2Rs 3Cs Skills Content validity index (CVI) was 1.00 and cronbach’s alpha coefficient was .97. The data were analyzed using descriptive statistic, paired t-test, and independent t-test. The results of the study showed that 1) The mean cognitive Skills in the experimental group after receiving an evidence-based teaching method was significantly higher than before receiving evidence-based teaching and higher than those in the control group received lecture and case study. 2) The mean 21st century skills in the experimental group after receiving an evidence-based teaching method was significantly higher than before receiving evidence-based teaching and higher than those in the control group received lecture and case study. Therefore, Evidence-Based Teaching strategies that should be used to promotes the Cognitive Skills and 21st century skills of the nursing students.